Arrangement of Blockchain Technology as an Effort to Prevent Payment Fraud via the Indonesian Standard Quick Response Code (Qris) Performed by Consumers in Electronic Transactions - Abel Yehud Silalahi; Adlia Nur Zhafarina (IHSA Institute, 2024)
This research discusses the use of blockchain technology as a solution to reduce the risk of fraud in electronic transactions using QRIS in Indonesia. With the development of information technology, cybercrime such as online fraud is increasing. However, existing regulations have not fully addressed this problem. The research method used is normative-empirical legal research, which combines literature study and interviews with QRIS users. The results show the need for better legal protection to protect consumers from fake QRIS and system vulnerabilities. The findings highlight that blockchain technology provides advantages in creating unparalleled transparency and security in electronic transactions, thus providing an effective solution in reducing the risk of fraud. Interviews with QRIS users also revealed their challenges and expectations regarding the use of QRIS, emphasizing the importance of public education on the correct use of QRIS as well as proactive law enforcement. This shows the importance of further exploration to create a fair digital transaction environment for consumers and businesses, as well as emphasizing cooperation between the government, regulatory agencies, and industry players in improving legal protection and public education regarding QRIS